SIAE Rare Variants in Juvenile Idiopathic Arthritis and Primary Antibody Deficiencies - Eirini Sevdali; Elena Tsitsami; Maria Tsinti; Evangelia Farmaki; Efimia Papadopoulou-Alataki; Anastasios E. Germenis; Matthaios Speletas (Journal of Immunology Research)
Sialic acid acetylesterase (SIAE) deficiency was suggested to lower the levels of ligands for sialic acid-binding immunoglobulin-like receptors, decreasing the threshold for B-cell activation. In humans, studies of rare heterozygous loss-of-function mutations in SIAE gene in common autoimmune diseases, including juvenile idiopathic arthritis (JIA), yielded inconsistent results. Considering the distinct pathogenesis of the two main subtypes of JIA, autoinflammatory systemic (sJIA) and autoimmune oligo/polyarticular (aJIA), and a predisposition to autoimmunity displayed by patients and families with primary antibody deficiencies (PADs), the aim of our study was to analyze whether SIAE rare variants are associated with both the phenotype of JIA and the autoimmunity risk in families with PADs. A cohort of 69 patients with JIA, 117 healthy children, 54 patients, and family members with PADs were enrolled in the study. Three novel SIAE variants (p.Q343P, p.Y495X, and c.1320+33T>C) were found only in patients with aJIA but interestingly also in their healthy relatives without autoimmunity, while none of PAD patients or their relatives carried SIAE defects. Our results show that SIAE rare variants are not causative of autoimmunity as single defects.